PERAN SKEMA WARNA KOMPLEMENTER UNTUK PENGUATAN MOOD DAN LOOK DALAM FILM AMÉLIE - Dwi Cahyo, Adam; Yeni Astuti, Soekma; Haryanto, Dwi (Institut Seni Budaya Indonesia Bandung, 2024)
The film Amelie is a romantic comedy film from France. The film Amelie tells the story of a shy waitress who tries to change her identity to become a valuable person in the surrounding community. The film Amelie presents beautiful visuals with contrasting colors that are harmonious or complementary in the artistic elements. The complementary color scheme of the film Amelie is characteristic and conveys the mood and look of comedy and romantic genre films. The research method used was a qualitative descriptive method with a literature study to analyze the role of complementary color schemes in the artistic elements of strengthening the mood and look of the film Amelie. The research data is in the form of the film Amelie with analysis techniques in the form of data reduction, data presentation and drawing conclusions. Complementary color schemes reinforce seven types of mood and look, namely earthy, playful, provocative, robust, tribal, power-clashing, and active. The role of complementary color schemes in artistic elements can strengthen the mood and look of a film so that the atmosphere and feel of the story in a film become stronger and more memorable.